Evaluation of Caregiving Burden in Caregivers of Children with Chronic Disease - Murat Doğan; Utku Özer; Tuğçe Kalın; Yılmaz Seçilmiş; Mehmet Adnan Öztürk (Galenos Yayinevi, 2021)
Introduction:We aimed to evaluate the epidemiological characteristics of caregivers and caregiving burden of caregivers of children with chronic diseases who were admitted to the pediatric emergency unit and to evaluate the relationship between them.Methods:A prospective study was conducted with caregivers of 146 patients aged 0-18 years with chronic disease. Zarıt burden interview (ZBI) was used to evaluate the caregiver burden.Results:The ZBI median scores of caregivers was 33 (4-74). Caregiver burden was moderate in 21.9% and heavy in 7.5% of caregivers. The median age of the children who were given care was 72 (12-216) months. 57.5% of the patients were boys and 42.5% were girls. Neurological, oncological and metabolic diseases constituted the first three of the children's disease group. The median duration of the disease was 36 (6-210) months. The median age of caregivers was 35 (18-65) years. Of the caregivers, 138 (94.5%) were female and 8 (5.5%) were male. The median of illness duration was 36 (6-210) months. The marital status of the caregivers was married (92.5%), divorced (6.8%) and single (0.7%), respectively. The educational status of caregivers was primary education (56.2%), high school (29.5%) and university (14.4%), respectively. The most common jobs of caregivers were housewives (81.5%), public servants (12.3), self-employed (4.8%) and unemployed (1.4%). No significant correlation was found between the burden of care and the age, gender, marital status, proximity of the caregiver, and duration of caregiving (p>0.05). Those who were housewives were more burdened with care (p<0.05). In those with moderate to severe care burden, later disease development and economic difficulties were greater and education levels were lower (p<0.05).Conclusion:Care burdens should be reduced by providing more economic and social support to those who care for the child with chronic disease and by educating healthcare professionals on issues such as disease management, problem solving and coping with stress.